Trends and Future Directions of Accreditations in Higher Education : Bibliometric Analysis - Srikanth Reddy, J.; Sharma, Ritu; Kumar Gupta, Amit (Prabandhan: Indian Journal of Management, 2023)
Purpose : The study aimed to highlight the importance of accreditation in higher education and its relevance in enhancing the quality and standardization of the education system. The purpose of this research was to analyze the trends and future directions of accreditation in higher education using bibliometric analysis. Specifically, the study aimed to identify the relationship between accreditation-originating countries and top publishing countries in this domain, assess the relevance of accreditation over time, and propose future research areas through citation analysis and thematic evaluation. Design/Methodology/Approach : The bibliometric method was used in our research to study and explore accreditation in higher education research. Bibliometric analysis is famous for quantitative data analysis. Using the relevant keywords in the Scopus database, we performed a bibliometric analysis on 1,544 articles. We used the biblioshiny tool through â€œRâ€ open-source software for performance analysis and thematic mapping analysis, and VOSviewer was used for co-occurrence keyword analysis and network analysis. Findings : The findings of the analysis substantiate with literature to infer the relationship between accreditation-originating countries and top countries publishing in this domain. The findings revealed that the relevance of accreditation has been increasing over the years, and the accreditation-originating countries were leading the research through publications in this area. The study proposed future research areas using citation analysis and thematic evaluation. Practical Implications : The implications are relevant to higher education institutes, policymakers, and other stakeholders. The study is expected to be a catalyst in driving the research in the area of accreditation in higher education. Novelty : This study's novelty is its use of bibliometric analysis to explore the trends and future directions of accreditations in higher education. The study also highlighted the increasing relevance of accreditation in enhancing the quality and standardization of the education system. The study is expected to be a catalyst for driving research in the area of accreditations in higher education.